Microstructures, mechanical properties and corrosion resistance of sprayed Ca–P coating for micropatterning carbon/carbon substrate surface. Issue 6 (15th April 2020) - Su, Yangyang; Li, Kezhi; Wang, Jing
Abstract: Carbon/carbon (C/C) surface micropatterning is a method of modifying the surface into the complete and regular geometry. In this work, we introduce a positive effect on bonding strength between sprayed Ca–P coating and surface micropatterning C/C substrate. Interestingly, C/C substrate coated by Ca–P coating provides textured surface for a new bone ingrowth. The sprayed Ca–P coating is then subjected to microwave-hydrothermal (MH) treatment with the aim of eliminating surface defects and obtaining a uniform purity phase. These objectives were achieved in our previous study by the MH method. The molar ratio of Ca/P in the coatings is nearly close to 1, which is far below that of Ca/P for hydroxyapatite (Ca10 (PO4 )6 (OH)2, HA, 1.67). The purpose of this article is to transform the phases in the sprayed Ca–P coating, which owns the better bioactivity and high corrosion resistance. In order to raise the molar ratio of Ca/P, the coatings are treated under high-temperature (around 700 °C). They are analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and a fourier transform infrared spectra (FTIR). The bonding strength (coating/substrate), biological activity and corrosion resistance of the coatings are investigated. The resulting coatings own the different microstructures and phase compositions from the original sprayed Ca–P coating. Especially, results show that the shear strength of the sprayed Ca–P coating deposited on surface micropatterning C/C substrate increases by 61% which is more than that of the coating on non-surface micropatterning C/C substrate. Additionally, high-temperature treated coating presents a good biological activity and an excellent corrosion resistance of current density (1.3078 × 10 -6 A/cm 2 ) and potential (−0.17 VSCE ).